Recurrence of Pelvic Chondrosarcoma through Fascial Defect into Abdominal Cavity - Kemal Gökkuş; Tolgay Akin; Ergin Sagtas; Murat Saylik; Ahmet Turan Aydın (Case Reports in Oncological Medicine)
Our patient was a 76-year-old female who has been operated on 2 times in 8 years for pelvic chondrosarcoma. The patient came to our clinic with a large mass in left iliac region which extended into the paravertebral area. Physical examination and preoperative imagining studies revealed a mass at the left iliac area that infiltrated sciatic notch and extended from posterior iliac region towards the anterior side of iliac bone through the sciatic notch and an incisional hernia including descending colon. The mass was also penetrating the abdominal cavity through the hernia. Surgical intervention was planned. Since the tumor infiltrated the sciatic nerve, hemipelvectomy was indicated. Patient refused hemipelvectomy. Therefore, palliative debulking surgery was considered. We treated the case with marginal excision and abdominal wall reconstruction employing prolene and vicryl suture materials in order to prevent a postoperative visceral herniation and local invasion. At the latest follow-up appointment in 2 years, the patient still had no signs of tumor recurrence. This case showed us that an incisional hernia can serve as a pathway for the recurrence invasion of the chondrosarcoma.